Mixed-ligand complexes of creatinine and L-glutamic acid with Co(II), Cu(II), Mn(II): Potentiometric studies - (:unkn) unknown (FREUND PUBLISHING HOUSE LTD, 2007)
Creatinine, an important bioligand, and its main tautometric forms include donor groups with strong coordination capacity In this study, the stability constants of binary and mixed ligand complexes formed by creatinine and L-glutamic acid -with Co(II), Cu(II), Mn(II) were determined by the Calvin-Bjerrum and Irving-Rossotti methods.
Keywords: L-glutamic acid; creatinine; cobalt; copper; manganese complex; ligand; MOLECULAR-STRUCTURE; L-ASPARAGINE; CRYSTAL; BINARY